Metallic interconnects for solid oxide fuel cell: A review on protective coating and deposition techniques. (6th April 2017) - Mah, Joelle C.W.; Muchtar, Andanastuti; Somalu, Mahendra R.; Ghazali, Mariyam J.
Abstract: With the reduction of solid oxide fuel cells (SOFCs) operating temperature to the range of 600 °C–800 °C, metallic alloy with high oxidation resistance are used to replace traditional ceramic interconnects. Metallic interconnects is advantageous over ceramic interconnects; in terms of manufacturability, cost, mechanical strength, and electrical conductivity. To date, promising candidates for metallic interconnects are all Cr-containing alloys, which are susceptible to volatile Cr migration that causes cell degradation. As such, protective coatings have been developed to effectively inhibit Cr migration; as well as maintain excellent electrical conductivity and good oxidation resistance. This article reviews the progress and technical challenges in developing metallic interconnects; different types of protective coatings and deposition techniques for metallic interconnects for intermediate-temperature SOFC applications. Highlights: Developing interconnect materials with good Cr retention capability is the main technological limitation in planar SOFCs. Ferritic stainless steel is preferred due to its oxidation resistance, electrical conductivity, manufacturability and cost. Great potential in composite spinel coating, despite the occurrence of spallation between coating/substrate interfaces. Electrodeposition is effective in fabricating metallic interconnects for intermediate-temperature SOFC applications.